POLITICAL WILL: MACRO RESPONSE TO THE CONCERNS OF PRIMARY HEALTH CARE IN INDIA - Priyanka Yadav (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The Pandemic of 2020 posed a serious challenge for the healthcare system across the globe. Indian health care system was severely hit and questioned for its quality of services majorly at public health level. The pandemic was a unlike situation where the best health care systems have failed to deliver. However, with respect to the Indian health care system the pandemic exposed as the shortcomings and inadequacies ranging from primary to tertiary level. Economic liberalization of the 1990s affected the Indian health care infrastructure to an extent which led to the transition of health care from a right to a commodity. Health care services soon became a thing of trade (Baru, 2003). Under this scenario public health system of the country witnessed a steep decline and more so primary health care which is the backbone of the health infrastructure. The decline situation continues even today because of which there is observed shift towards private health care services even when the out-of-expenditure is high. However, this shift cannot be normalized as complete state withdrawal from the health sector can widen the socio-economic gap in country. Neoliberal policies and practices require a macro solution to micro level problem marring the health sector in India. This paper aims to locate the macro solution in the concept of political will which can be instrumental in tackling the challenges faced by the Indian health care sector in neoliberal times.